Development of technology and development of production of reinforcement no. 6 of strength class A500S form 2f in coils according to the requirements of GOST 34028–2016 - S. A. Savchenko; S. M. Volosovich; A. A. Kuchkov; I. V. Astapenko; A. B. Sychkov (Литьë и металлургия)
The article presents the results of research on the development and mastery of the technological process of rolling reinforcement in coils with a nominal diameter of 6 mm of strength class A500C of a double‑sided periodic profile of the 2f form, ensuring the required mechanical properties, improving complex quality indicators based on improving the chemical composition and technological modes of two‑stage cooling on the Stelmor line taking into account its cooling and transporting abilities. A method of hot rolling of reinforcement with a double‑sided crescent (2f) profile is proposed; technological factors influencing the strength, plastic and operational properties of reinforcing bars through the formation of its effective microstructure are considered. The chemical composition of steel was proposed and modes of thermomechanical hardening of reinforcement with rolling heating were developed, providing high consumer properties. The results of mechanical tests of rolled reinforcing bars in coils and comparative data on the mechanical properties and geometric parameters of the reinforcement are also presented.